An evaluation of the collection of the Development Bank of the Philippines and Landbank libraries with implications for collection development - Bongco, Antonio Jose D. (1998)
The primary aim of this study is to evaluate the collection of the Development Bank of the Philippines and Landbank and to find out if these libraries meet the needs of its clientele. The study made use of the quantitative and qualitative methods. Instruments used were the questionnaires administered to the library users and an interview guide for the interviews conducted with the head librarians. Visits to these institutions made the researcher gather other information like the library's budget, growth rate, and expenditures. Problems encountered by these libraries were also included.